CHILDREN'S REFERENCE UNITS REPRESENTED BY PHYTONYMS - Giyosova Vasilaxon Avazxon qizi (Web of Journals Publishing, 2024)
This article describes the representation of the thematic classification of children's reference units by phytonyms.
Keywords: phytonym, reference units, dialogic speech, poetic speech, linguistic culture, speech communication, ethnic culture.